Participatory Demonstration and Evaliation of Food Barley (Hordeum vulgare L.) varieties at Adami Tulu Jido kombolcha district, Central rift valley of Oromia, Ethiopia - Tesfaye Gemechu; Fiseha Tadesse; Hikma Sultan (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2020)
Two improved food barley varieties (Gobe and Bentu) were demonstrated along with local check as a follow up of participatory variety selection activity. The objectives were to demonstrate and evaluate the performance of the varieties along with their management practices under farmers' circumstances and to raise farmers' knowledge and skill on food barley production and management practices. Sites were selected in collaboration with respective district agricultural offices. Trainings were given for farmers, Development Agents and experts and other stakeholders. The Participating farmers were also capacitated through follow up exchange visits and field days. Recommended seed and fertilizer rate were used for the demonstration trial establishment. According to the results, there was no statistically significant yield difference between the varieties at (p<0.05). However, both Gobe and Bentu varieties have shown higher yield advantage over local variety showing a yield advantage of 62% and 11.5% over the local variety respectively.